Idirl Johna Yencha jako próba rozwinięcia języka uniwersalnego G.W. Leibniza - Kulczycki, Emanuel (Wydawnictwo Fundacji Humaniora, 2009)
The purpose of the article is to present John Yench’s apriori language as a continuation of Leibniz’s idea. Before I proceed to show the project of Inter-Disciplinary International Reference Language, I would like to discuss development of Gottfried Wilhelm Leibniz’s view on an artificial language. I will try to show the evolution of Leibniz’s universal language: from the ideal calculation to a tool which will formalize the whole human knowledge. Also, I will show Leibniz’s influence on further ideas of artificial language. I will compare his projects with Yench’s language – Idirl. Analysis of Idirl’s main assumptions will be useful to show the degree of continuation of Leibniz’s ideas in the apriori language of John Yench.
Keywords: Leibniz; Philosophy of Language; Język uniwersalny; Idirl; John Yench; Wieża babel